Effect of Extracorporeal Shock Wave Therapy Combined with Kinesio Taping on Plantar Fasciitis - Mingliang JIN; Hua YUAN; Xu HU; Xu JIN; Hongru YUAN; Jiajin FAN (康复学报)
Objective:To explore the clinical effect of extracorporeal shock wave therapy (ESWT) combined with kinesio taping (KT) in the treatment of plantar fasciitis (PF).Methods:A total of 87 patients who met the clinical diagnosis standard of plantar fasciitis were randomly divided into control group, ESWT group and ESWT+KT group, with 29 cases in each group. The control group received routine rehabilitation treatment, including low-power He-Ne laser, ultrasonic therapy, exercise therapy (triceps of the leg, plantar fascia relaxation). The ESWT group only received shock wave therapy. The ESWT+KT group was treated with ESWT and KT simultaneously. Visual analogue scale (VAS), American Orthopedic Foot and Ankle Society (AOFAS) ankle and hind foot function score and Berg balance scale were assessed before treatment (T0), one week after treatment (T1), four weeks after treatment (T4), and eight weeks'follow up after treatment ended (T12) in the three groups to evaluate the pain of foot, function of foot and ankle and the balance function of lower extremity respectively.Results:Before treatment, there was no significant difference in VAS score, AOFAS score and Berg score among the three groups (P> 0.05). During the treatment, 4 patients were dropped (2 cases in the control group, 1 case in the ESWT group and 1 case in the ESWT+KT group). Compared with T0time point, the VAS scores of the three groups were significantly lower at T1and T4time points respectively (P< 0.05). The VAS score of the ESWT+KT group was lower than that of the ESWT group (P< 0.05), and that of the ESWT group was lower than that of the control group (P< 0.05). Compared with T0time point, AOFAS scores of the three groups were significantly improved at T1and T4time points respectively (P< 0.05). The AOFAS score of the ESWT+KT group was higher than that of the ESWT group (P< 0.05), and that of the ESWT group was better than that of the control group (P< 0.05). Compared with T0time point, the Berg scores of the three groups were significantly improved at T1and T4time points respectively (P< 0.05). The Berg score of the ESWT+KT group was better than that of the ESWT group respectively (P< 0.05), and the ESWT group was better than that of the control group (P< 0.05). The VAS score of the control group was higher than that of T4time point (P> 0.05), AOFAS score and Berg score were lower than those of T4time point (P> 0.05), the VAS score of the ESWT group was lower than that of T4time point (P< 0.05), AOFAS score and Berg score were lower than those of T4time point (P> 0.05), the VAS score of the ESWT+KT group was lower than that of T4time point (P< 0.05), AOFAS score and Berg score were higher than those of T4time point (P< 0.05).Conclusion:ESWT combined with kinesio taping can significantly improve the ankle function of patients with plantar fasciitis, relieve pain, improve the ability of balance and walking, and maintain the short-term, medium-term and long-term effect after treatment, which is worthy of clinical application.